2012
DOI: 10.1016/j.febslet.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of measles virus phosphoprotein at S86 and/or S151 downregulates viral transcriptional activity

Abstract: a b s t r a c tMeasles virus phosphoprotein (P protein) is a cofactor of the viral RNA polymerase (L protein) that associates with the nucleoprotein-RNA complex to support viral transcription and replication. Here, we report a significant inverse correlation between the phosphorylation level of MV-P protein and viral transcriptional activity. Upregulation of P protein phosphorylation resulted in reduction of viral transcription. Additionally, we found that strong phosphorylation at S86 and S151 of P protein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…We previously demonstrated that the major phosphorylation sites of N protein (S479 and S510) are involved in various stages of the viral life cycle (28,29). Additionally, we found that a mutant with mutation of both major phosphorylation sites remained phosphorylated but to a lesser extent, suggesting that unidentified phosphorylation sites exist within the N protein.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We previously demonstrated that the major phosphorylation sites of N protein (S479 and S510) are involved in various stages of the viral life cycle (28,29). Additionally, we found that a mutant with mutation of both major phosphorylation sites remained phosphorylated but to a lesser extent, suggesting that unidentified phosphorylation sites exist within the N protein.…”
Section: Discussionmentioning
confidence: 81%
“…Whether N proteins were expressed by a plasmid or during viral replication (46), the phosphorylation rate of the threonine residue in NC was almost the same. Thus, T279 phosphorylation of the N protein is required for the maintenance of the herringbone-like structure of NC, and T279 is different from the major phosphorylation sites that take part in the functional regulation of viral gene expression (27)(28)(29). Electron microscopy demonstrated that NC has a helical structure with approximately 13 to 14 N proteins per turn (15,50,51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also showed that the major phosphorylation sites of the N protein are indirectly involved in the regulation of viral transcription by changing the phosphorylation status of the P protein (17). In the present study, we rescued recombinant MV (rMV) HL strains (18) of these N-phosphorylation sites (S479A, S510A, and S479A/S510A) using a reverse genetics system that we had previously established (19) and investigated their influence on virus growth.…”
Section: Easles Virus (Mv) Amentioning
confidence: 85%